Quantitative analysis on porosity of reactive powder concrete based on automated analysis of back-scattered-electron images. (February 2019) - Edwin, Romy Suryaningrat; Mushthofa, Mushthofa; Gruyaert, Elke; De Belie, Nele
Abstract: In this study an automated analysis of back-scattered-electron images (SEM-BSE) for segmentation of the porosity of reactive powder concrete is presented, making use of Matlab. The development of the proposed threshold method is based on a classification of the images according to two different brightness levels, which correspond to low and high grey value thresholds. The intersection point of the tangent lines in the area segmented versus grey value curve is used as the upper threshold to determine threshold 1 and threshold 2 and the resulting pore volume is validated with mercury intrusion porosimetry. Nevertheless, a difference between porosities obtained by SEM-BSE and MIP can be expected, because the first method can measure all pore types, while the second will only measure open pores. The result shows that the use of the proposed threshold method achieves a good correlation with MIP for pore segmentation in the RPC microstructure.